The Effect of Employee Competence on Organizational Performance - Wawan Gunawan; Agung Surya Dwianto (ARMADA : Jurnal Penelitian Multidisiplin, 2026)
The manufacturing industry, particularly the electronics sector, plays an important role as a driver of the national economy and a catalyst for global competitiveness. One of the strategic factors that determine the success of an organization is employee competence. Therefore, this study aims to analyze how employee competence affects organizational performance at PT Jaya Refrigeration Equipment. This study uses a quantitative approach with proportionate stratified random sampling technique. The research population includes 520 employees of PT Jaya Refrigeration Equipment, with a sample size of 84 respondents determined using the Slovin formula. The research instrument is a questionnaire distributed via g-form. The data was then analyzed using simple linear regression through SPSS version 27. The results showed that employee competence had a positive and significant effect on organizational performance (p-value 0.001 < 0.05). The correlation coefficient (R) value of 0.896 indicates a very strong relationship between the two variables, while the coefficient of determination (R²) of 0.803 shows that employee competence can explain 80.3% of the variation in organizational performance. These results confirm that improving employee competence is a key factor in driving the optimization of organizational performance in the manufacturing sector.